PERKEMBANGAN ISTILAH "PENDIDIK": DARI ERA KLASIK HINGGA MODERN - Assa Dullah Rouf; Wedra Aprison (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This article conducts an analysis of the development of the term "educator" from classical to modern times. By examining the thoughts and concepts that emerge in educational literature, we trace the evolution of the meaning and role of educators in the context of classical Islamic history. The aim of this article is to provide a profound understanding of how the concepts of education and the role of educators have evolved over time.